Epidendrum tripunctatum (Orchidaceae, Laeliinae): the tale of two species - Higgins, Wesley (2015)
Homonyms can often create confusion and this is the case with Epidendrum tripunctatum. A new combination, Prosthechea micropus, is required to correct the misapplied nomenclature. The author recognizes the Brazilian species as Prosthechea punctifera and the Central American species is recognized as Prosthechea micropus.